Me’phaa, Women, Resistance and Sense of Place in the Displacements of Exactivism and Drug Trafficking - Erika Sebastián Aguilar (Íconos)
This article studies, from the theoretical framework of community feminisms, the sense of place and resistance built by me’phaa women in relation to the chains of violence unfolding from the Canadian mining project Camsim Minas SA de CV and the criminal group of drug trafficking Los Ardillos in Xochiatenco, Guerrero, Mexico. It centers on understanding how the me’phaa indigenous women are surrounded by dynamics of terror and threatened by the displacements caused by narco-mining, as well as on how they face gender violence in the interior of their communities. Nevertheless, these women construct resistances from their sense of community place and position themselves in the systems of indigenous communal government. This research is the result of a qualitative methodology approach, historiographical studies, and an ethnography developed. The findings expose the reconfigurations of the sense of body-land-territory and the debates over gender inequalities women experience in the interior of their communities.